High-tap-density spherical ferric sodium pyrophosphate electrode material and preparation method thereof

Through solution gel method and spray drying combined with ion doping technology, the problems of uneven mixing materials and low tap density in NFPP synthesis were solved, and spherical sodium ferrophosphate pyrophosphate electrode material with high tap density and excellent electrochemical performance were achieved. The preparation of sodium ion batteries is suitable for the commercial prospects.

CN119191256APending Publication Date: 2024-12-27QINGDAO UNIV OF SCI & TECH
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411395132.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the synthesis of traditional NFPP, the uneven precursor mortar mixture is prone to occur, and the low tap density of the material cannot meet large-scale applications. NFPP has low electronic conductivity and slow diffusion kinetics.

Method used

The solution gel method is used to obtain sodium ferric pyrophosphate precursor, achieving uniform mixing of sodium, potassium, iron, phosphorus and carbon sources at the molecular level, and high-tap density spherical phosphoric acid is prepared by presintering and spray drying. Sodium ferric pyrophosphate electrode material combined with ion doping technology to improve electrochemical performance.

Benefits of technology

The tap density, electrochemical performance and cycle stability of the material were improved, and the tap density was increased from 0.87g/cm3 to 1.25g/cm3, and the capacity retention rate reached 85.28% after 800 cycles, which significantly improved the electrode material. Application performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191256A_ABST
    Figure CN119191256A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of electrode materials, and particularly relates to a high-tap-density spherical ferric sodium pyrophosphate electrode material and a preparation method thereof. According to the preparation method, a uniform precursor is prepared by utilizing solution gel, and a strategy of combining spray drying with secondary sintering is adopted, so that uniform carbon coating and doping modification of ferric sodium pyrophosphate can be successfully realized, and the strategy provides an important experimental basis for an industrialization process of a sodium ion battery. And the method has great potential of large-scale preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the technical field of electrode material preparation, and in particular relates to a high-tap density spherical sodium iron phosphate pyrophosphate electrode material and a preparation method thereof. Background technology:

[0002] Since sodium-ion batteries have similar electrochemical properties to the traditional lithium-ion batteries we are familiar with, and my country has abundant sodium resources and low prices, sodium-ion batteries have become a practical and effective alternative to lithium-ion batteries, showing commercial prospects in the field of large-scale energy storage. Among them, NFPP, as a polyanion positive electrode material for sodium-ion batteries with great commercial prospects, has advantages such as high theoretical capacity and stable structure, but its low electronic conductivity and slow diffusion kinetics limit the practical application of NFPP. Therefore, the selection of appropriate ions for doping broadens the Na + The diffusion path reduces the Na + The diffusion barrier is to increase the electronic conductivity of NFPP and Na + An efficient approach to diffusion dynamics.

[0003] In addition, the phase purity, electrochemical properties and tap density of NFPP obtained by different synthesis methods also have certain differences. At present, the methods for synthesizing NFPP mainly include solid phase method, sol-gel method, spray drying method, etc. Among them, the solid phase method mainly involves mixing the reactants and calcining them at high temperature to cause a solid phase reaction to generate the target product. The advantages of this method are simple equipment and easy operation, but its disadvantages are also obvious, such as slow reaction speed, incomplete reaction, low product purity, and high energy consumption. The sol-gel method is to hydrolyze and polymerize the reactants in the solution to form a sol, and then obtain the target product by drying and calcining. The advantage of this method is that high-purity and uniform products can be obtained, but the disadvantage is that the reaction conditions are harsh and the operation is relatively complicated. The above methods all have certain shortcomings, especially the low tap density of the material cannot meet the large-scale application of NFPP. Summary of the invention:

[0004] The technical problem to be solved by the present invention is that impurities are easily generated due to uneven mixing of precursor mortar during the traditional NFPP synthesis process.

[0005] In order to solve the above problems, the present invention uses a solution gel method to obtain a sodium iron phosphate pyrophosphate precursor, realizes a uniform mixing of a sodium source, a potassium source, an iron source, a phosphorus source and a carbon source at a molecular level, and solves the problem of uneven mixing from the source. Through the pre-sintering strategy, impurities in the material can be effectively removed, and the gas release during the final sintering process can be reduced, thereby reducing defects and improving the tap density of the material to a certain extent. In addition, uniform carbon coating of primary nanoparticles can be achieved. The pre-sintered product is further mixed with a carbon source and ground into nano-scale primary particles by ball milling and sand milling, and then granulated by spray drying. In addition to achieving uniform carbon coating of the primary and secondary particles of sodium iron phosphate pyrophosphate, the gas generated by citric acid during thermal decomposition can also be discharged through the tiny pores between the primary particles, avoiding the formation of bubbles inside the particles, and indirectly increasing the tap density of the material. Compared with the NFPP prepared by directly spray drying the precursor solution and then sintering at high temperature, the tap density of the NFPP prepared by this synthesis strategy is 0.87g / cm 3 Directly increase to 1.25g / cm 3 .

[0006] In addition, in order to solve the low electronic conductivity and slow diffusion kinetics of NFPP itself, the present invention uses ion doping to select K with a larger ion radius. + Appropriate replacement of Na + It can effectively broaden the ion diffusion path, thus greatly improving the electrochemical performance, and K can be doped into the Na site as a pillar ion, which helps to enhance the structural stability of the material, which is crucial for maintaining performance during long-term cycling. + Doping can introduce Na vacancies, thereby improving problems such as low electronic conductivity and poor charge transfer ability of electrode materials.

[0007] To achieve the above object, the present invention is implemented by the following technical scheme: a method for preparing a spherical sodium iron phosphate pyrophosphate electrode material with high tap density, comprising the following steps:

[0008] (1) Mix sodium source: potassium source: iron source: phosphorus source: carbon source in a stoichiometric ratio of 4-X:X:3:4:2, add deionized water in a mass ratio of 5:1, heat and stir to dissolve until the solution is in a gel state, and dry; the present invention obtains a sodium iron pyrophosphate precursor by using a solution gel method, and realizes a uniform mixing of sodium source, potassium source, iron source, phosphorus source and carbon source at the molecular level, which helps to obtain a more uniform precursor material and avoids problems such as phase impurity caused by uneven mixing. At the same time, we use K with a larger ionic radius + Partially replace Na + It can effectively broaden the ion diffusion path, thereby greatly improving the electrochemical performance, and K can be doped into the Na site as a pillar ion, which helps to enhance the structural stability of the material, which is crucial for maintaining performance during long-term cycling.

[0009] (2) The dried precursor obtained in step (1) is placed in a mortar, fully ground, placed in a porcelain boat and transferred to a tube furnace for pre-sintering, and kept at 350°C for 4 hours at a heating rate of 2°C / min in a pure argon environment to obtain a black powder product; the black powder and the second carbon source are added to a ball mill at a mass ratio of 5:1, and deionized water is added as a grinding aid at a mass ratio of 5:1, and ball milled at 550rpm for 3 hours; the ball-milled mixed material is transferred to a sand mill and sand milled at 400rpm for 2 hours to obtain a mortar; by means of pre-sintering, impurities in the material can be effectively removed, and gas release during the final sintering process can be reduced, thereby reducing defects and increasing the tap density of the material. In addition, by accurately controlling the stoichiometric ratio of the raw materials during the experiment, the purity of the product can be further improved while ensuring the expected structure of the product.

[0010] (3) spraying the mortar obtained after sand grinding in step (2) and spray drying; placing the powder obtained by spray drying in an agate mortar and lightly grinding; spray drying is widely used in various chemical and material science fields as an efficient material synthesis technology. Similarly, spray drying is suitable for the preparation of sodium iron phosphate pyrophosphate positive electrode materials, but in the actual production process, there are still disadvantages such as uneven material particle size, impure phase and low tap density, which makes it difficult to fully utilize the capacity of sodium iron phosphate pyrophosphate materials. The pre-sintered product is further mixed with a carbon source and ground into nanometer-scale primary particles by ball milling and sand milling. Granulating it by spray drying can achieve uniform carbon coating of sodium iron phosphate pyrophosphate primary nanoparticles and construct a three-dimensional conductive carbon network on the surface and inside of secondary micron-scale spherical particles assembled from primary particles, further enhancing the conductivity and cycle stability of the sodium iron phosphate pyrophosphate composite material.

[0011] (4) The powder obtained in step (3) was transferred to a tube furnace for secondary high-temperature sintering, and kept at 550°C for 8 hours at a heating rate of 2°C / min in a pure argon environment, in order to achieve uniform carbon coating of the primary / secondary particles of the material and further improve the crystallinity of the material. After natural cooling, the final black powder product N was obtained. 4-x K x FPP / C, that is, high tap density spherical sodium iron pyrophosphate electrode material.

[0012] Furthermore, the sodium source in step (1) and step (2) is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium pyrophosphate, sodium citrate, and anhydrous sodium acetate; the iron source is one or more of ferrous oxalate, ferrous nitrate, ferrous acetate, ferrous sulfate, ferrous chloride, and ferric phosphate; the potassium source is one or more of potassium chloride, potassium carbonate, potassium nitrate, potassium nitrite, and potassium sulfate; the phosphorus source is one or more of phosphoric acid, diammonium phosphate, diammonium hydrogen phosphate, pyrophosphate, and sodium pyrophosphate; and the first and second carbon sources are one or more of citric acid, glucose, oxalic acid, fructose, starch, ascorbic acid, and sucrose.

[0013] Furthermore, after adding deionized water and mixing in step (1), the solution is placed on a heated stirring table and heated and stirred at a speed of 300 r / min and a temperature of 70° C. until the material is fully dissolved, and stirring is continued until the solution is in a gel state, which is then transferred to a culture dish and dried in a forced air oven at 80° C. for 24 h.

[0014] Furthermore, step (3) is sprayed at a peristaltic pump speed of 30 Hz, the air inlet temperature of the spray drying is set to 260° C., and the air outlet temperature is set to 120° C. By using nozzles of different calibers, hollow spherical sodium iron phosphate pyrophosphate with tiny gaps of different particle sizes can be obtained. The spherical morphology is conducive to improving the tap density of the material. In addition, the hollow structure and the tiny gaps between the primary particles can provide a certain specific surface area, increase the contact area with the electrolyte, and effectively shorten the transmission path of ions and electrons, thereby improving the power density and energy density of the battery.

[0015] A high tap density spherical sodium iron phosphate pyrophosphate electrode material prepared by the above method, namely N 4- x K x FPP / C. The obtained material has a capacity retention rate of 85.28% at 1C rate after 800 cycles, and the capacity can still reach 86.3 mAh g -1 , showing excellent cycle performance.

[0016] An application of the above electrode material, wherein the positive electrode is made of N 4-x K x FPP / C, acetylene black, and PVDF are composed in a ratio of 8.5:1:0.5. The diaphragm is made of glass fiber, the current collector is made of aluminum foil, the negative electrode is made of sodium sheet, the electrolyte is 1MNaClO4, the solvent is a mixture of EC and DEC in a mass ratio of 1:1, and the additive is 2% FEC by mass. The button battery is assembled in an argon atmosphere, an oxygen-free and water-free glove box.

[0017] The beneficial effects of the present invention are:

[0018] (1) The present invention first uses a solution gel method to obtain a sodium iron phosphate pyrophosphate precursor, achieves uniform mixing of the sodium source, potassium source, iron source, phosphorus source and carbon source at the molecular level, and performs pre-sintering to achieve uniform carbon coating of the primary particles. Subsequently, the pre-sintered product is uniformly mixed with the second carbon source and granulated by spray drying and secondary sintering to construct a three-dimensional conductive carbon network for the secondary micron-sized spherical particles. In addition, combined with the modification strategy of ion doping, the conductivity and cycle stability of the sodium iron phosphate pyrophosphate composite material are effectively enhanced on the basis of ensuring the material's tap density and phase purity. This synthesis strategy has obvious advantages and broad application prospects in the preparation of high-performance pure-phase NFPP positive electrode materials.

[0019] (2) The industrialization of sodium-ion battery cathode materials is imminent. As a type of cathode material, polyanionic compounds have extremely high industrialization prospects. Among them, iron-based polyanionic cathode materials are more abundant in the earth's crust than vanadium-based polyanionic cathode materials, with low cost and environmental friendliness. Although vanadium reserves are relatively abundant, vanadium compounds have certain toxicity and can cause harm to the environment and require special treatment. In addition, they are more expensive than iron, which makes iron-based cathode materials have obvious economic benefits in commercial applications. Na4Fe3(PO4)2P2O7 (NFPP), as an emerging composite phosphate cathode material in recent years, has the advantages of both NaFePO4 and Na2FeP2O7, and its performance exceeds that of the two materials alone. It has a high theoretical capacity of 129mAh / g, a low sintering temperature (<600℃) and low energy consumption during the production process. NFPP is very stable in the air, environmentally friendly and non-toxic, and low in price, meeting the requirements of green chemistry and sustainable development. The above characteristics make NFPP one of the most promising materials in the future energy storage field.

[0020] (2) As a special material preparation technology, spray drying can complete the synthesis of materials in just a few minutes, greatly improving production efficiency. In addition, the preparation of precursors by the solution gel method can achieve uniform mixing of sodium source, potassium source, iron source, phosphorus source and carbon source at the molecular level, effectively avoiding the problem of phase impurity caused by uneven material distribution of precursors prepared by traditional spray drying, which is crucial to stabilizing the phase purity of the subsequently prepared sodium iron phosphate pyrophosphate. In addition, deionized water is used as a grinding aid instead of ethanol, which has certain safety risks, during the ball milling process of the pre-sintered product, which greatly avoids the occurrence of safety hazards.

[0021] (3) For the phosphate iron pyrophosphate material prepared by spray drying, reducing the hollow structure space inside the particles is an effective measure to improve the tap density of the material. For the traditional synthesis method of directly spray drying the precursor solution and then sintering at high temperature, the sprayed solution has a phenomenon that the solvent on the surface of the droplets evaporates rapidly under the high temperature environment during the spraying process, and the internal solvent is often not completely evaporated. In this case, it is easy to form a large hollow structure inside the particles. In addition, the gas generated by citric acid during the thermal decomposition process cannot escape from the surface of the particles in time during the subsequent heat treatment process, causing bubbles to form inside the particles and causing volume expansion, further reducing the tap density of the material. Through the pre-sintering strategy, impurities in the material can be effectively removed and gas release during the final sintering process can be reduced, thereby reducing defects and improving the tap density of the material to a certain extent. In addition, the pre-sintered product is further mixed with a carbon source and ground into nano-scale primary particles by ball milling and sand milling, and then granulated by spray drying. In addition to achieving uniform carbon coating of the primary and secondary particles of sodium ferric pyrophosphate, the gas generated by the thermal decomposition of citric acid can also be discharged through the tiny pores between the primary particles, avoiding the formation of bubbles inside the particles and indirectly increasing the tap density of the material. Compared with the NFPP prepared by directly spray drying the precursor solution and then sintering at high temperature, the tap density of the NFPP prepared by this synthesis strategy is 0.87 g / cm 3 Directly increase to 1.25g / cm 3 .

[0022] (4) Although NFPP has attracted widespread attention due to its high theoretical capacity and stable structure, as a polyanion cathode material, it still has low electronic conductivity and Na + Therefore, we use ion doping to select K with a larger ion radius. + Appropriate replacement of Na + It can effectively broaden the ion diffusion path, thereby greatly improving the electrochemical performance, and K can be doped into the Na site as a pillar ion, which helps to enhance the structural stability of the material, which is crucial for maintaining performance during long-term cycling. In addition, an appropriate amount of K+ doping can introduce Na vacancies, thereby improving problems such as low electronic conductivity and poor charge transfer ability of electrode materials. After appropriate K doping, NFPP has a reversible capacity of 114.1 mAh / g at 0.2C. K-doped NFPP also has excellent cycle stability, and its capacity retention rate can reach 85.28% after 800 cycles at 1C, showing excellent industrial prospects. Description of the drawings:

[0023] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0024] Figure 1 This is a SEM image of the sodium iron pyrophosphate N4-xKxFPP / C material prepared in the embodiment of the present application;

[0025] Figure 2 This is the XRD pattern of the sodium iron pyrophosphate N4-xKxFPP / C material prepared in the embodiment of the present application;

[0026] Figure 3 As shown, it is a charge and discharge curve diagram of the sodium iron pyrophosphate N4-xKxFPP / C material prepared in the embodiment of the present application at 0.2C;

[0027] Figure 4 This is a rate performance diagram of the sodium iron pyrophosphate N4-xKxFPP / C material prepared in an embodiment of the present application;

[0028] Figure 5 This is the 1C cycle performance diagram of the sodium iron pyrophosphate N4-xKxFPP / C material prepared in the embodiment of the present application. Specific implementation method:

[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Unless otherwise specified, all raw materials in the following examples were commercially available.

[0031] Embodiment 1:

[0032] A method for preparing a spherical sodium iron phosphate pyrophosphate electrode material with high tap density comprises the following steps:

[0033] S1: The sodium source is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium pyrophosphate, sodium citrate, and anhydrous sodium acetate; the iron source is one or more of ferrous oxalate, ferrous nitrate, ferrous acetate, ferrous sulfate, ferrous chloride, and ferric phosphate; the potassium source is one or more of potassium chloride, potassium carbonate, potassium nitrate, potassium nitrite, and potassium sulfate; the phosphorus source is one or more of phosphoric acid, diammonium phosphate, diammonium hydrogen phosphate, pyrophosphate, and sodium pyrophosphate; the first and second carbon sources are one or more of citric acid, glucose, oxalic acid, fructose, starch, ascorbic acid, and sucrose.

[0034] S2: Mix the sodium source: potassium source: iron source: phosphorus source: carbon source in S1 in a stoichiometric ratio of 4-X:X:3:4:2 in a beaker, add deionized water in a mass ratio of 5:1, place it on a heated stirring table, heat and stir at a speed of 300 r / min and a temperature of 70°C until the material is fully dissolved, continue stirring until the solution is in a gel state, transfer it to a culture dish, and dry it in a forced air oven at 80°C for 24 hours.

[0035] S3: Put the dried precursor into a mortar and grind it thoroughly for 30 minutes. Place it in a porcelain boat and transfer it to a tube furnace for pre-sintering. Keep it at 350°C in a pure argon environment at a heating rate of 2°C / min for 4 hours to obtain a black powder product. Add the black powder and the second carbon source to a ball mill at a mass ratio of 5:1, and add deionized water as a grinding aid at a mass ratio of 5:1, and ball mill at 550rpm for 3 hours. Transfer the material mixed by ball milling to a sand mill and sand mill at 400rpm for 2 hours.

[0036] S4: The mortar obtained after the above sand grinding was sprayed at a peristaltic pump speed of 30Hz. The air inlet temperature of the spray drying was set to 260℃, and the air outlet temperature was set to 120℃. Spray drying was performed under this setting parameter. The powder obtained by spray drying was placed in an agate mortar and lightly ground. The powder was transferred to a tubular furnace for secondary high-temperature sintering. The temperature was kept at 550℃ for 8h at a heating rate of 2℃ / min in a pure argon environment. The purpose was to achieve uniform carbon coating of the primary / secondary particles of the material and further improve the crystallinity of the material. After natural cooling, the final black powder product N was obtained. 4-x K x FPP / C.

[0037] Embodiment 2:

[0038] The positive electrode is made of N obtained in Example 1 4-x K x FPP / C, acetylene black, and PVDF are composed in a ratio of 8.5:1:0.5. The diaphragm is made of glass fiber, the current collector is made of aluminum foil, the negative electrode is made of sodium sheet, the electrolyte is 1MNaClO4, the solvent is a mixture of EC and DEC (mass ratio 1:1), and the additive is 2% FEC by mass. The button battery is assembled in an argon atmosphere, an oxygen-free and water-free glove box.

[0039] Verification results:

[0040] like Figure 1 As shown, the sodium iron pyrophosphate N prepared in step (4) 4-x K xSEM image of FPP / C material; it can be seen from the figure that the prepared sodium iron pyrophosphate N 4-x K x FPP / C material is a spherical structure with a particle size of about 3-20μm. The uneven particle size distribution can effectively increase the material's tap density, and the material's tap density can reach up to 1.25g / cm 3 , and the hollow structure with tiny gaps can provide a certain specific surface area, which is conducive to the full infiltration of the electrolyte, which makes the material have excellent electrochemical properties.

[0041] like Figure 2 As shown, the sodium iron pyrophosphate N prepared in step (4) 4-x K x XRD diagram of FPP / C material. The data results show that the N 4-x K x All the diffraction peaks of FPP / C are in good agreement with those of Na4Fe3(PO4)2P2O7 (PDF#89-0579), which proves that the doping of potassium ions does not introduce new peaks and that the samples prepared by spray drying are pure and free of impurities. 4-x K x The sharp characteristic peaks of XRD of FPP / C confirm that the prepared sample has good crystallinity.

[0042] like Figure 3 As shown, the sodium iron pyrophosphate N prepared in step (4) 4-x K x The charge-discharge curve of FPP / C material at 0.2C. From the charge-discharge curve of the sample between 2.0-4.5V, two pairs of obvious voltage platforms can be observed, located at around 2.9V and 3.2V, respectively. The redox peaks at 2.88 / 2.96V correspond to the insertion / deinsertion of Na3, and the redox peaks at 3.15 / 3.24V correspond to the insertion / deinsertion of Na1 and Na4 in N 4-x K x Insertion / extraction in FPP / C structure. The discharge capacity can reach about 114.1 mAh / g at 0.2C.

[0043] like Figure 4 As shown, the sodium iron pyrophosphate N prepared in step (4) 4-x K x The rate characteristics of the electrode of FPP / C material at current densities of 0.2 to 20C. When the current density is 0.2C, 0.5C, 1C, 5C, 10C, 15, and 20C, N 4- x K xThe discharge specific capacities of the FPP / C positive electrode are 115.6mAh / g, 108.4mAh / g, 102.6mAh / g, 78.4mAh / g, 60.6mAh / g, 55.1mAh / g, and 48.3mAh / g, respectively. (Theoretical specific capacity 129mAh / g), proving that the sample has an excellent rate performance. When the current returns to 0.2C, there is no significant difference between its specific capacity and the initial capacity, and the coulombic efficiency of the sample is basically maintained at 100%, indicating that the material has good stability and reversibility.

[0044] like Figure 5 As shown, the sodium iron pyrophosphate N prepared in step (4) 4-x K x The cycling performance diagram of the FPP / C material electrode at 1C. After 800 cycles at 1C, its discharge capacity is 86.3mAh / g, and the capacity retention rate can reach 85.28%, indicating that the material has excellent cycling stability.

[0045] In summary, the method of synthesizing a hollow spherical micron-sized sodium iron pyrophosphate positive electrode material with controllable particle size by using a spray drying method and selecting a modification technology of multiple carbon coatings combined with alkali metal ion doping has the advantages of fast reaction speed, complete reaction, high product purity, simple equipment, and easy operation.

[0046] The method of preparing a precursor by a solution gel method for pre-sintering and the method of synthesizing NFPP by a spray drying method for di-sintering are proposed in the present invention, and the method of preparing a precursor by a solution gel method for pre-sintering and the method of synthesizing NFPP by a spray drying method are proposed in the present invention. + Doping improves Na + Diffusion dynamics, types and ratios of the sodium source, iron source, potassium source, phosphorus source, first carbon source, second carbon source, temperature and rotation speed of the solution gel, ball milling speed and duration, sand milling speed and duration, concentration of ball milling slurry, peristaltic pump speed, inlet and outlet temperatures, heat treatment temperature and time, etc. are all protected by the present invention.

[0047] The above-mentioned technical steps, experimental dosage, experimental materials, temperature and speed of solution gel, ball milling speed and duration, sand milling speed and duration, concentration of ball milling slurry, stirring time, stirring rate, peristaltic pump speed, preheating time, inlet and outlet temperature, heat treatment temperature, heat treatment time, air flow rate, etc., including but not limited to the innovative details in the above-mentioned contents are all within the scope of protection of the invention.

Claims

1. A method for preparing a spherical sodium iron phosphate pyrophosphate electrode material with high tap density, characterized in that The following steps are involved: (1) mixing a sodium source, a potassium source, an iron source, a phosphorus source, and a carbon source in a stoichiometric ratio of 4-X:X:3:4:2, adding deionized water in a mass ratio of 5:1, heating and stirring to dissolve the solution until the solution is in a gel state, and drying; (2) The dried precursor obtained in step (1) is placed in a mortar, fully ground, placed in a porcelain boat and transferred to a tube furnace for pre-sintering, and kept warm at 350°C for 4 hours at a heating rate of 2°C / min in a pure argon environment to obtain a black powder product; the black powder and the second carbon source are added to a ball mill at a mass ratio of 5:1, and deionized water is added as a grinding aid at a mass ratio of 5:1, and ball milled at 550 rpm for 3 hours; the ball-milled mixed material is transferred to a sand mill and sand milled at 400 rpm for 2 hours to obtain a mortar; (3) spraying the mortar obtained after sand grinding in step (2) and spray drying it; placing the powder obtained by spray drying in an agate mortar and lightly grinding it; (4) The powder obtained in step (3) was transferred to a tube furnace for secondary high-temperature sintering, and kept at 550°C for 8 h at a heating rate of 2°C / min in a pure argon environment. After natural cooling, the final black powder product N was obtained. 4-x K x FPP / C, that is, high tap density spherical sodium iron pyrophosphate electrode material.

2. The method according to claim 1, characterized in that: The sodium source in step (1) and step (2) is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium pyrophosphate, sodium citrate, and anhydrous sodium acetate; the iron source is one or more of ferrous oxalate, ferrous nitrate, ferrous acetate, ferrous sulfate, ferrous chloride, and ferric phosphate; the potassium source is one or more of potassium chloride, potassium carbonate, potassium nitrate, potassium nitrite, and potassium sulfate; the phosphorus source is one or more of phosphoric acid, diammonium phosphate, diammonium hydrogen phosphate, pyrophosphate, and sodium pyrophosphate; and the first and second carbon sources are one or more of citric acid, glucose, oxalic acid, fructose, starch, ascorbic acid, and sucrose.

3. The method according to claim 1, characterized in that: After adding deionized water and mixing in step (1), the solution is placed on a heated stirring table and heated and stirred at a speed of 300 r / min and a temperature of 70° C. until the material is fully dissolved, and stirring is continued until the solution is in a gel state, which is then transferred to a culture dish and dried in a forced air oven at 80° C. for 24 h.

4. The method according to claim 1, characterized in that: Step (3) sprays the material at a peristaltic pump speed of 30 Hz, and the air inlet temperature of the spray drying is set to 260° C., and the air outlet temperature is set to 120° C. By using nozzles of different calibers, hollow spherical sodium iron phosphate pyrophosphate with tiny gaps of different particle sizes can be obtained. The spherical morphology is conducive to improving the tap density of the material. In addition, the hollow structure and the tiny gaps between the primary particles can provide a certain specific surface area, increase the contact area with the electrolyte, and effectively shorten the transmission path of ions and electrons, thereby improving the power density and energy density of the battery.

5. A high tap density spherical sodium iron phosphate pyrophosphate electrode material N prepared by any method of claims 1-4 4- x K x FPP / C.

6. An electrode material N as claimed in claim 5 4-x K x The application of FPP / C is characterized by: The positive electrode is made of N 4- x K x FPP / C, acetylene black, and PVDF are composed in a ratio of 8.5:1:0.

5. The separator is made of glass fiber, the current collector is made of aluminum foil, the negative electrode is made of sodium sheet, the electrolyte is 1M NaClO4, the solvent is a mixture of EC and DEC in a mass ratio of 1:1, and the additive is 2% FEC by mass. The button battery is assembled in an argon atmosphere, an oxygen-free and water-free glove box.

Citation Information

Cited By

  • Sodium ferric phosphate pyrophosphate positive electrode material, preparation method thereof and battery

    CN119528107A

  • Preparation method of high-compaction-density ferric sodium pyrophosphate positive electrode material

    CN120964759A

  • High-compaction-density ferric sodium pyrophosphate positive electrode material, preparation method thereof and positive electrode plate

    CN121698320A

  • A high-compaction-density sodium iron phosphate pyrophosphate positive electrode material, a preparation method thereof and a positive electrode plate

    CN121698320B